The LMACTrach, a Aew Approach for Endotracheal Intubation: Apilot Study in 100 Patients Undergoing Elective Surgery - Valiollah Hassani; Maryam Zafarghandi; Mohammad Farhadi (Medical Journal of The Islamic Republic of Iran, 2010)
Backgroundand endotracheal intubation under direct vision in both anticipated and unexpecteddifficult intubation situations.: The LMA CTrach system is a new device for airway managementMethodsdifferent types of elective surgeries. After randomly selecting the patients for intubationwith this new device, the airway characteristics, height,weight, dental overbiteand thyromental distance were all evaluated before induction.Our goal was to exploreprimarily the success rate of intubation with LMACTrach.:We used this system in 100 patients undergoing general anesthesia forResultsall 100 patients. Nonetheless,successful tracheal intubation was performed in 95 patients.Among our patients,2 had Mallampati grade IV airways with short necks,body mass index(BMI) > 30, and without the capability to bite their upper lips.Amazingly both patients were intubated with this method,proving a device as an assuringapproach in cases of difficulty with ventilation and intubation. Of all patients,44 were females and 56 males.The mean age was 34 ± 2 years. BMI measured for allpatients was 20-25 except for two cases who had BMI > 30.: We were able to insert LMA CTrach and provide optimal ventilation inConclusionand vocal cords during intubation even in difficult cases,it can be assumed that thisdevice is a precious aid as equal as fiberoptic bronchoscopy for the anesthesiologists.:Since the LMA CTrach provided us with direct view of the larynx